Doses of iron in prevention and treatment of anemia in pregnant women: an ongoing debate - Neogi, Sutapa B. (Indian Journal of Community Health, 2018)
Iron supplementation during pregnancy, both as a preventive and therapeutic measure has been a matter of debate. The guiding principles behind supplementation include availability of adequate iron stores before pregnancy, diet during pregnancy and concomitant infections. No country performs routine screening of iron stores by measuring ferritin and the decision to supplement iron is largely based on haemoglobin (Hb) levels. Evidence suggests that Hb content of the mother’s blood between 95 and 105 g/l in the third trimester correlates with the best clinical outcome. Effectiveness of routine iron supplementation during pregnancy for improving maternal hematological indices exists, but the clinical significance for both pregnant women and infants remains unclear. In the absence of conclusive evidence, several developed nations follow an individual based approach by evaluating the iron stores and then deciding on the course of treatment. On the other hand, in developing countries, where the baseline prevalence of anemia is high, existing data supports routine iron supplementation as a safe strategy to prevent maternal anemia. Controversies exist around the most appropriate dosage and frequency (daily v/s weekly) of iron supplementation for both preventive and therapeutic purposes because increased doses does not necessary yield better haematological and clinical outcomes. On the contrary, excess doses may be associated with more side effects and also may produce oxidative stress, release of free radicals, may interfere with the absorption of divalent cations, may block iron absorption by upregulating hepcidin and may result in hemoconcentration further leading to adverse outcomes. This document gives a snapshot of the existing evidence and provides a case for further deliberations on the most appropriate dosage for iron supplementation during pregnancy giving due weightage to epidemiological, physiological and clinical requirements.